LAZIMKANLAH YANG BENAR, JANGAN SELALU MEMBENARKAN YANG LAZIM, KARENA YANG LAZIM TIDAK SELALU BENAR,SALAH KAPRAH DALAM PEMAKAIAN BAHASA INDONESIA - Ni Luh Yaniasti (Universitas Panji Sakti, 2022)
AbstractIndonesian language users in official forums are expected to use Indonesian in accordance with applicable rules, both in spoken and written form. In accordance with the reality, currently there are still uses of Indonesian that are not in accordance with the rules of good and correct Indonesian or also known as standard language. This study was expected to be able to broaden Indonesian speakers to gain knowledge and to understand the rules for using the Indonesian language properly and correctly. The method used in obtaining data was observation method with note-taking techniques. Furthermore, the data obtained were analyzed using descriptive qualitative interpretive analysis methods. Based on data analysis, it can be seen that in the use of Indonesian there are forms of language that are misguided, such as ambiguous/contaminated sentences, wrong diction, and wrong reasoning. In this regard, the author suggests that Indonesian language users must pay attention to and comply with good and correct Indonesian language rules to create a dignified language and be proud to use Indonesian in accordance with what is mandated by the 1945 Constitution, namely in chapter XV, article 36.Keywords: Misguided, Standard Indonesian